Trigeminocardiac Reflex in Embolization of Intracranial Dural Arteriovenous Fistula - Lv, X.; Li, Y.; Lv, M.; Liu, A.; Zhang, J.; Wu, Z. (American Journal of Neuroradiology, 2007)
SUMMARY: We report a case of immediate reproducible and reflexive response of asystole upon stimulation of Onyx injection during embolization of a tentorial dural arteriovenous fistula in a 53-year-old man. Upon recognition of the reflexive relationship between Onyx injection and increased vagal tone, the patient was given anticholinergic in an effort to block cholinergic hyperactivity. After atropine was given, no further dysrhythmias occurred.